Father Resilience in Siak District, Riau Province - Novianti, Ria; Puspitasari, Enda (Proceedings of the UR International Conference on Educational Sciences, 2018)
Father play important role in children live. Not only to fullfil children needs but also to take care and protect his children. In Indonesia, some fathers do his main role as a breadwinner and often leave the responsibility to raise the children to mother who takes the role to raise the children and spent most of the time with them. But there are still fathers who are involved in child rearing. To do so, father should be able to overcome stress and bounce back from difficulties, which called resilience. Because stress and problems can affect the relation between father and children that make him unable to create warm and loving relation with children. The aims of this research is to describe fatherâs resilience in Siak Kecil District. The sample in this research are 347 father who has children between age 0-6 years old. The methodology used is descriptive quantitative approach. Result that can be concluded from the data analysis, the higher percentage of resilient indicators is reaching out 89, 09% the lowest percentage is emotion regulation 72.09%.Fathers is able to be related with others and ask for support when required.But they still need to develop the abilty to control emotion to be able to have a healthy relationship with others, especially their children.